2009
DOI: 10.1016/j.ydbio.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Early thyroid development requires a Tbx1–Fgf8 pathway

Abstract: The thyroid develops within the pharyngeal apparatus from endodermally-derived cells. The many derivatives of the pharyngeal apparatus develop at similar times and sometimes from common cell types, explaining why many syndromic disorders express multiple birth defects affecting different structures that share a common pharyngeal origin. Thus, different derivatives may share common genetic networks during their development. Tbx1, the major gene associated with DiGeorge syndrome, is a key player in the global de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…This suggests that the final thyroid size is constrained by the number of cells initially recruited to a thyroid fate. Other examples of development of thyroid hypoplasia associated with a reduced size of the early primordium are the hand2 hypomorphic allele (han c99 ) and fgf8 mutant (ace) in zebrafish (Wendl et al, 2007) and the Tbx1 null mouse embryo (Lania et al, 2009), the effects of which will be discussed in further detail below. Direct evidence for this novel concept of developmental regulation comes from a recent study demonstrating that the number of progenitor cells in the pancreatic bud is limiting final organ size (Stanger et al, 2007).…”
Section: Nodal Signaling and Early Regulation Of Thyroid Sizementioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that the final thyroid size is constrained by the number of cells initially recruited to a thyroid fate. Other examples of development of thyroid hypoplasia associated with a reduced size of the early primordium are the hand2 hypomorphic allele (han c99 ) and fgf8 mutant (ace) in zebrafish (Wendl et al, 2007) and the Tbx1 null mouse embryo (Lania et al, 2009), the effects of which will be discussed in further detail below. Direct evidence for this novel concept of developmental regulation comes from a recent study demonstrating that the number of progenitor cells in the pancreatic bud is limiting final organ size (Stanger et al, 2007).…”
Section: Nodal Signaling and Early Regulation Of Thyroid Sizementioning
confidence: 99%
“…Disruption of the Shp2-binding sites of the FGF receptor (FGFR) docking protein FRS2 causes thyroid hypoplasia (Kameda et al, 2009), indicating that embryonic thyroid growth is influenced by FGFR signaling. In view of the significant impact genetic deletion of Tbx1, a transcriptional regulator of FGFs (Vitelli et al, 2002), has on thyroid size in late morphogenesis (Fagman et al, 2007), early thyroid development was investigated in embryos where Tbx1 was either generally deleted or specifically targeted in the mesoderm (Mesp1 Cre/+ ;Tbx1 fl/-) (Lania et al, 2009). This showed that proliferation in the E8.5 foregut endoderm and the number of cells in the thyroid placode is reduced by mesodermal ablation of Tbx1 suggesting a diminished thyroid precursor cell pool size.…”
Section: Role Of Fgf and Bmp Signaling In Early Thyroid Developmentmentioning
confidence: 99%
See 3 more Smart Citations